Survey of duplicate detection using progressive detection techniques - Venkatraman, K; Akila, A (International Journal of Engineering and Technology, 2018)
Data is an important task in real world; the common data is represented and used in all the fields. The duplicate data is executed and displayed in scenario. The proposed work two types of techniques used first one Progressive Sort Neighbourhood Method (PSNM) and Progressive Blocking (PB). Progressive Sort Neighbourhood Method is used to deliver the exact input based output and the method will separate the input based keywords and check the similarity of the output data. The progressive blocking is to filter the irrelevant information, keywords based indexing and entry level filtering standard input is implemented based on user requirement.